2007
DOI: 10.1177/152660280701400503
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of the Iliac Arteries after Endovascular Abdominal Aortic Aneurysm Repair and Suitability of Ectatic Iliac Arteries as a Distal Sealing Zone

Abstract: Dilatation of the CIA is significant after EVAR, and it is more pronounced in ectatic iliac arteries. Although ectatic iliac arteries appear to be suitable sealing zones in the short term, continued follow-up is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 24 publications
(35 reference statements)
1
40
0
Order By: Relevance
“…4 At the level of the distal iliac necks, there appears to be a dilatation, yet only a few studies have investigated the subject. 5 We do not know, however, if the dilatations develop in parallel (ie, affecting the proximal and distal necks in the same proportions) or if they have two distinct evolutions. In addition, we do not know whether the dilatation concerns only the anchor zone, based on which the endoprosthesis diameter was chosen, or if it encompasses the adjacent vascular segments covered by the endoprosthesis.…”
mentioning
confidence: 98%
“…4 At the level of the distal iliac necks, there appears to be a dilatation, yet only a few studies have investigated the subject. 5 We do not know, however, if the dilatations develop in parallel (ie, affecting the proximal and distal necks in the same proportions) or if they have two distinct evolutions. In addition, we do not know whether the dilatation concerns only the anchor zone, based on which the endoprosthesis diameter was chosen, or if it encompasses the adjacent vascular segments covered by the endoprosthesis.…”
mentioning
confidence: 98%
“…However, continued expansion of an uncovered CIA is seen following EVAR. 25 The data presented here would predict a CIA Ͼ16 mm may exceed 18 mm within 2-3 years, which may explain the increased in type 1b endoleak seen in some series. 5,17 Alternatives for larger CIA aneurysms include extension into the external iliac artery or an iliac bifurcation device.…”
Section: Discussionmentioning
confidence: 88%
“…11,12 The incidence of differing diameters of common iliac artery landing sites in a population of patients undergoing EVAR has recently been published. 13 This study reported a significantly greater number of larger common iliac arteries, which exhibit accelerated dilatation compared with those iliac arteries of smaller diameter. However, we were unable to confirm this trend in our study as the diameters of all but one iliac artery lay within the normal range at the time of EVAR.…”
Section: Discussionmentioning
confidence: 96%